Effect of hyperbaric oxygen therapy on cerebral vasospasm: a vascular morphometric study in an experimental subarachnoid hemorrhage model - ZİYAL, MUSTAFA İBRAHİM; BOZKURT, SÜHEYLA; ŞEHİRLİ, ÜMİT SÜLEYMAN (TAYLOR & FRANCIS LTD, 2014)
This study was undertaken to investigate the preventive or therapeutic effect of hyperbaric oxygen therapy (HBOT) on cerebral vasospasm following experimental subarachnoid hemorrhage (SAH). Twenty rabbits were assigned randomly to one of four groups. Animals in Group I were not subjected to SAH or sham operation (control group, n = 5). Animals in Group II were subjected to sham operation and received no treatment after the procedure (sham group, n = 5). Animals in Group III were subjected to SAH and received no treatment after SAH induction (SAH group, n = 5). Animals in Group IV were subjected to SAH and received five sessions of HBOT at 2.4 atmospheres absolute (ATA) for 2 h (treatment group, n = 5). Animals were euthanized by perfusion and fixation 72 h after procedures. Basilar artery vasospasm indices, arterial wall thicknesses, and cross-sectional luminal areas were evaluated. Statistical comparisons were performed using Kruskal-Wallis and Mann-Whitney U tests. Mean basilar artery vasospasm index in the treatment group was significantly smaller than in the SAH group. Mean basilar artery wall thickness in the treatment group was significantly smaller than in the SAH group. Mean basilar artery cross-sectional luminal area in the treatment group showed an increase relative to the SAH group, but this difference remained statistically insignificant. Our results demonstrated that repeated application of HBOT at 2.4 ATA for 2 h attenuated vasospastic changes such as increased vasospasm index and arterial wall thickness. HBOT is thus a promising candidate for SAH-induced vasospasm. Further studies are needed to evaluate maximal effect and optimal application regimen.
Keywords: Cerebral vasospasm; hyperbaric oxygen; subarachnoid hemorrhage; vascular morphometry; vasospasm index; wall thickness; INTERCELLULAR-ADHESION MOLECULE-1; MONOCLONAL-ANTIBODY; ENDOTHELIAL-CELLS; RHOA/RHO-KINASE; BASILAR ARTERY; RAT MODEL; EXPRESSION; INFLAMMATION; ISCHEMIA; APOPTOSIS